(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE To assess the causes of abdominal pain among patients presenting in the emergency department of Abbasi Shaheed Hospital Karachi. METHODOLOGY A cross-sectional design study was employed at the Department of Surgery, Abbasi Shaheed Hospital / KMDC, Karachi, on a cohort of 160 patients aged 18 to 60 years of either gender presented with acute abdominal pain. Each patient underwent a CT scan to confirm the cause of their acute abdominal pain. Data was interpreted and evaluated through SPSS version 26, with a p-value of ≤0.05 considered statistically significant. RESULTS The mean age of the patients was found as 36.07 ± 7.29 years. Out of 160 patients, males were 62 (38.7%) and females were 98 (61.3%). The causes of acute abdominal pain were noted as renal calculi (20%), hernia (3.75%), hepatitis (2.5%), ruptured ectopic (1.25%), acute appendicitis (25.6%), acute cholecystitis (6.8%), bowel obstruction (8.12%), bowel perforation (4.37%), colitis (1.8%), constipation (5%), cystitis (3.12%), decompensated liver disease (5.62%), gallstones (6.25%), inflammatory bowel disease (1.87%), liver abscess (3.75%), ovarian cyst (3.12%), ovarian torsion (0.6%), pancreatitis (9.37%), peptic ulcer (3.75%), testicular torsion (2.5%), and ectopic pregnancy (5%). CONCLUSION It is to be concluded that acute appendicitis, renal calculi, and pancreatitis was noted as the most frequent causes of acute abdominal pain. Future studies in multiple study centers with larger sample sizes are required to validate the findings of current study.